Model Kepemimpinan Transformasional dan Transaksional Serta Aplikasinya dalam Pendidikan Islam - Zaky Mubarok; Sunarto Sunarto (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This research is a literature review that examines various literature on the implications of transformational and transactional leadership. The purpose of this study is to determine the implementation of transformational and transactional leadership for Islamic educational institutions, as well as the similarities and differences in transformational and transactional leadership behaviors. The method used in this study is library research, using a qualitative approach with a rational approach method. The findings of this study show that transformational and transactional leadership have implications for each individual's commitment to organizational values and goals. Transformational leadership builds long-term relationships, while transactional leadership builds short-term relationships with subordinates based on shared goals and rewards are given when subordinates are able to achieve goals. Instead, sanctions are given if the objectives cannot be achieved. Creative and innovative behavior is not the main thing, but the status quo is considered important. Islamic education leaders can combine these two models to create a balance between innovation and achievement of results.